2012
DOI: 10.1074/jbc.m112.397570
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based Analyses Reveal Distinct Binding Sites for Atg2 and Phosphoinositides in Atg18

Abstract: Background: Atg18 plays a critical role in autophagy as a complex with Atg2 and phosphatidylinositol 3-phosphate. Results: The structure of the Atg18 paralog was determined, and important residues in Atg18 were identified. Conclusion: Atg18 recognizes Atg2 and membranes using distinct regions. Significance: This study will be a basis for elucidating the function of Atg18 in autophagy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
158
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 120 publications
(176 citation statements)
references
References 40 publications
17
158
1
Order By: Relevance
“…The Atg18 β1-β2 loop and β2-β3 loop in blade 2 are important for PAS targeting [151]. Blade 2 is located at the opposite position to blade 5 and blade 6, and thus is not involved in membrane docking.…”
Section: Atg9 Complexmentioning
confidence: 99%
See 2 more Smart Citations
“…The Atg18 β1-β2 loop and β2-β3 loop in blade 2 are important for PAS targeting [151]. Blade 2 is located at the opposite position to blade 5 and blade 6, and thus is not involved in membrane docking.…”
Section: Atg9 Complexmentioning
confidence: 99%
“…Blade 2 is located at the opposite position to blade 5 and blade 6, and thus is not involved in membrane docking. Additional studies indicate that the loops in blade 2 are important for Atg18-Atg2 interaction [151,154], allowing a refinement of the model for Atg18 membrane binding. While Atg18 binds to the membrane through blades 5 and 6, blade 2, which is located on the opposite side of the protein, interacts with Atg2.…”
Section: Atg9 Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to S. cerevisiae and K. lactis, which are widely used for molecular biology and industrial applications (Mattiazzi et al, 2012;Schaffrath and Breunig, 2000;Schwimmer et al, 2006;Smith and Snyder, 2006;van Leeuwen et al, 2012), K. marxianus has received relatively little attention, although there are an increasing number of reports describing the potential application of K. marxianus for the production of ethanol, biomass, endogenous enzymes and aromatic compounds (Bansal et al, 2008;Fonseca et al, 2008;Gao and Daugulis, 2009;Limtong et al, 2007;Nonklang et al, 2008Nonklang et al, , 2009Rodrussamee et al, 2011;Wittmann et al, 2002) and for protein structural analysis (Watanabe et al, 2012;Yamaguchi et al, 2012aYamaguchi et al, , 2012b. Thus, in the present study, we generated and characterized 79 auxotrophic mutants and identified 35 complementing genes using a novel integrative transformation approach for the development of genetic tools in K. marxianus.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several K. marxianus proteins, including the autophagy-related proteins KmAtg7, KmAtg10 and KmHsv2, have been applied to crystal structural analysis because the formation of crystals of the orthologous S. cerevisiae proteins was difficult (Watanabe et al, 2012;Yamaguchi et al, 2012aYamaguchi et al, , 2012b. However, the genetic and functional analyses of these and other K. marxianus proteins has not been performed in K. marxianus due to the lack of genetic techniques that are commonly available for conventional yeast species.…”
Section: Introductionmentioning
confidence: 99%